Improving Reading Comprehension Through Small Group Discussion - Adawiyah, Dita; Larasati, Finza (Universitas Nusantara PGRI Kediri, 2020)
Teaching technique is needed by every teacher in transferring knowledge to the students. It was a great role for the result of the teaching. This study aimed to to find out the significant difference in reading comprehension achievement between the students who were taught by using small group discussion and those who were not. The population was all the eleventh-grade students of SMA Negeri 9 Palembang which consisted of six classes with total number of 232 students. The total sample of the study was 74 students. Purposive sampling technique was used in collecting the sample. This study used experimental method with the type was quasi-experimental. The researcher collected the data through narrative reading test. The writer used the Statistical Package for the Sosial Sciences (SPSS) program to analyze the data to find out the way or the strategy in teaching reading comprehension through small gorup discussion. The first measurement used pre-test, the second used post-test. The experimental group was given treatment and the control group was not. The result showed that the students in experimental group performed better than the students in control group. It could be stated that improving students’ reading comprehension through small group discussion was more significant than conventional way to the eleventh garde students of SMA Negeri 9 Palembang.